2017
DOI: 10.3390/su9112109
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Hotel and Restaurant Electricity Consumption and Tourism in 11 European Union Countries

Abstract: Tourism is a major economic activity in the world. However, while tourism has a noticeable positive impact on economic development, it also contributes to environmental degradation by increasing energy consumption and therefore emissions. This paper analyzes the relationships between Hotel and Restaurant electricity consumption and tourism growth in 11 European Union countries for the period 2005-2012, for which there is sufficient data availability. Panel data techniques are used to test an electricity consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 77 publications
0
19
0
1
Order By: Relevance
“…ATBHs were chosen for this research as there are limited studies in the environmental literature focused on this type of small-scale accommodation. So far, most studies regarding water and energy saving measures in the tourism industry are focused on hotels [42,[97][98][99][100][101], as these firms usually have big accommodation capacities, intensive water and energy consumption, as well as high related costs. ATBHs meet additional challenges in implementing water and energy savings due to their size and limited financial power, but also due to the lower environmental attitudes and behaviors of their owner-managers.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…ATBHs were chosen for this research as there are limited studies in the environmental literature focused on this type of small-scale accommodation. So far, most studies regarding water and energy saving measures in the tourism industry are focused on hotels [42,[97][98][99][100][101], as these firms usually have big accommodation capacities, intensive water and energy consumption, as well as high related costs. ATBHs meet additional challenges in implementing water and energy savings due to their size and limited financial power, but also due to the lower environmental attitudes and behaviors of their owner-managers.…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…The tourist sector, despite the presently existent severe constraints imposed by the sanitary emergence, interests almost all the countries and must be considered as an important component of the world's economies, accounting for approximately 10% of total global gross domestic product (GDP), 7% of global trade and 11% of the world's employment [1,2], with a continuously rising trend [3,4]. Accordingly, tourism represent an important contributor to energy consumption both at global and European scale [5,6,7], most of which is consumed in space heating and/or air conditioning (up to 50%), followed by hot water and cooking [8,9]. Hence, tourism exercises a relevant impact on the environment, being responsible for about 5% of the global CO2 amount emitted by human activities [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…The energy consumption of the whole society is directly or indirectly affected by many factors. Up to now, many scholars have studied the factors affecting the energy consumption [3][4][5][6]. The problem of electricity consumption is a complex non-linear problem, for which so far scholars have proposed various prediction models, such as grey theory [7][8][9], multiple regression [10][11][12], and time series models [13][14][15]; In recent years, various intelligent algorithms have also been applied to power consumption prediction [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Castillo et al [5] used a unified data set of 13 income and expenditure household surveys to assess changes in electrical and electricity consumption, taking into account income distribution, GDP, population, etc. as indicators of impact assessment; Pablo-Romero [6] analyzed the relationship between electricity consumption and tourism growth in hotels and restaurants in 11 EU countries between 2005 and 2012, and modelled energy use based on three variables: energy price, income and climate. The result showed that both income and climate have a significant impact on increasing electricity consumption, while energy prices have no effect on electricity consumption.…”
Section: Introductionmentioning
confidence: 99%